Tourniquet‐induced lower limb ischemia/reperfusion reduces mitochondrial function by decreasing mitochondrial biogenesis in acute kidney injury in mice. Issue 3 (10th February 2022) - Packialakshmi, Balamurugan; Stewart, Ian J.; Burmeister, David M.; Feng, Yuanyi; McDaniel, Dennis P.; Chung, Kevin K.; Zhou, Xiaoming
Abstract: The mechanisms by which lower limb ischemia/reperfusion induces acute kidney injury (AKI) remain largely uncharacterized. We hypothesized that tourniquet‐induced lower limb ischemia/reperfusion (TILLIR) would inhibit mitochondrial function in the renal cortex. We used a murine model to show that TILLIR of the high thigh regions inflicted time‐dependent AKI as determined by renal function and histology. This effect was associated with decreased activities of mitochondrial complexes I, II, V and citrate synthase in the kidney cortex. Moreover, TILLIR reduced mRNA levels of a master regulator of mitochondrial biogenesis PGC‐1α, and its downstream genes NDUFS1 and ATP5o in the renal cortex. TILLIR also increased serum corticosterone concentrations. TILLIR did not significantly affect protein levels of the critical regulators of mitophagy PINK1 and PARK2, mitochondrial transport proteins Tom20 and Tom70, or heat‐shock protein 27. TILLIR had no significant effect on mitochondrial oxidative stress as determined by mitochondrial ability to generate reactive oxygen species, protein carbonylation, or protein levels of MnSOD and peroxiredoxin1. However, TILLIR inhibited classic autophagic flux by increasing p62 protein abundance and preventing the conversion of LC3‐I to LC3‐II. TILLIR increased phosphorylation of cytosolic and mitochondrial ERK1/2 and mitochondrial AKT1, as well as mitochondrial SGK1 activity. In conclusion, lower limb ischemia/reperfusion induces distal AKI by inhibiting mitochondrial function through reducing mitochondrial biogenesis. This AKI occurs without significantly affecting PINK1‐PARK2‐mediated mitophagy or mitochondrial oxidative stress in the kidney cortex. Abstract : Lower limb ischemia/reperfusion induces distal AKI by inhibiting mitochondrial function through reducing mitochondrial biogenesis. This AKI occurs without significantly affecting PINK1‐PARK2‐mediated mitophagy or mitochondrial oxidative stress in the mouse kidney cortex.